Contract Administration for Construction Professionals (Construction Economics and Building, 2022)
Coggins, J., Schwarz, S., Davies, M., and Ma, T.      Contract Administration for Construction Professionals.      LexisNexis Australia at www.lexis.com.au, 2022.      ISBN/ISSN 978-0-4093-5083-8 (Paperback, 588 pp) AUD 95, E-book, ISBN/ISSN 978-0- 9043-5084-5